Tuesday

March 31, 2015

March 31, 2015

Posted by **Anonymous** on Wednesday, November 28, 2007 at 10:02pm.

2 + 1/7 [x - (x+6 / 7) - 2]

This is what I have:

= 2 + 1/7 ( x -x-6/7 -2)

= 2 + (x - x - 6 - 2 / 49)

= (98 + x - x - 6 - 2) / 49

= 90/49

But the answer is:

6x + 78 / 49

- How do you properly distribute? -
**Reiny**, Wednesday, November 28, 2007 at 11:04pmI believe you meant to type:

2 + 1/7 [x - (x+6)/7 - 2]

= 2 + 1/7[(7x - x - 6 - 14)/7]

= 2 + 1/7[(6x - 20)/7]

= 2 + [(6x - 20)/49]

= 98/49 + (6x - 20)/49

= (98 + 6x - 20)/49

= (6x + 78)/49

watch how you place your brackets, it is extremely important

- How do you properly distribute? -
**Anonymous**, Wednesday, November 28, 2007 at 11:18pm= 2 + 1/7[(7x - x - 6 - 14)/7]

Can you explain how you distributed this part thoroughly?

- How do you properly distribute? -
**Anonymous**, Wednesday, November 28, 2007 at 11:21pmNevermind I got it

**Answer this Question**

**Related Questions**

functions - For each problem, construct two composite functions, . Evaluate each...

math - 2/3(7/8-4x)-5/8=3/8 I do not underdtand the steps?? Do I find a common ...

Physics - Can someone please show me step by step how to normalize e^-5x in the ...

Algebra 1--Step-by-Step - Can someone show me how to solve these step-by-step? ...

college algebra - Solve the following inequality. x^3+9x^2-108 less or equal to ...

English - It's time to do the group activity. I'll let you know how to do the ...

Physics - I'm trying to rearange this 0 = Xo + 2^-1 a t^2 for t I've been told ...

math - Can someone please show me step by step how to solve this, I've been ...

Dividing Rational Expressions - x^3-8/x^2-4 divided by (x^2+2x+4)/(x^3+8). This ...

TRIGONOMETRY - Can someone please show me step by step how to calculate the ...